A COMPREHENSIVE NEEDS ANALYSIS OF MARITIME ENGLISH FOR SHIP MACHINERY STUDENTS - Hafita, Yuniar Ayu; Sumarta, Ryan Puby; Riyanto, Budi; Sulistiono, Agus (Universitas Muhammadiyah Makassar, 2024)
Maritime English is essential for ensuring safety, efficiency, and effective communication in the global maritime industry, particularly for ship machinery students who require specialized language skills for technical and emergency situations. This study examines the specific needs of ship machinery students in Maritime English education, highlighting significant gaps in the current curriculum, especially in technical terminology and practical communication exercises for ship machinery operations and emergencies. A mixed-methods approach was utilized, involving 24 students and four professionals through questionnaires, interviews, and document analysis. Results indicate that 75% of students find the curriculum moderately effective, but 65% identify gaps in technical terminology, and 60% report inadequate real-life communication practice. Instructors emphasized the need for professional development to address these gaps. The study calls for a tailored curriculum based on English for Specific Purposes (ESP), integrating specialized content, practical exercises, and realistic simulations. It underscores the importance of continuous needs analyses and institutional support for curriculum enhancements, ensuring that Maritime English instruction remains relevant and effective in preparing students for their professional roles in the maritime industry. This approach will contribute to global maritime safety and efficiency by equipping ship machinery students with the necessary language skills.